Novel Anti-Microbial Metallic Surfaces for Infection Control - SARAH MARLEY (2021)
Hospital acquired infections pose a significant risk to patients, particularly the elderly and those who are immunocompromised. With the emergence of highly resistant pathogens it is more important than ever to reduce the potential for transmission. This study investigates reducing the likelihood for surfaces to act as a reservoir of bacterial transmission in hospitals by exploring the feasibility of antimicrobial coatings. The four bacteria most commonly found in hospital acquired infections were chosen for efficacy experiments (Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli and Klebsiella pneumoniae). Halloysite, naturally occurring aluminosilicate nanotubes, are biocompatible and have the ability to hold solutions within their lumen. These are hypothesised to be effective when incorporated into a coating as a slow release mechanism for disinfectants. Three disinfectants were chosen due to their chemical stability and approved contact safety for humans (Polyhexamethylene biguanide hydrochloride, Octenidine dihydrochloride and Chloroxylenol). The first portion of the study focused on bacterial adhesion and growth on steel discs, along with the minimum concentration of disinfectant required to inhibit cell growth. The second set of experiments looked at production of the disinfectant filled nanotubes and the resin coating on steel discs. The final experiments determined the antimicrobial efficacy of the nanotubes and coating on a qualitative level. The Gram-positive bacteria adhered more strongly to surfaces than the Gram-negative bacteria. Halloysite intercalated with chloroxylenol was effective at killing planktonic and plate-grown bacteria, whilst the remaining disinfectants were not. When incorporated into polyvinyl butyral resin, no disinfectant displayed antimicrobial properties. Immediate future work should focus on exploring the loading efficiency of the disinfectant and improving the coating method, along with testing various other disinfectants and polymers, considering porosity and particle dispersion during production. Overall, this study serves to successfully create a methodology for initial production of the coating and testing of its antimicrobial properties.